Water security in China–India relations: Pathways towards green diplomacy and sustainable development - Quang, Tran Tho; Kiet, Le Hoang; Anh, Dang Quynh; Tam, Le Thi Thanh (Journal of Water and Land Development, 2026)
This study investigates China’s hydropower and green development projects on the Brahmaputra River and their implications for India within the broader framework of hydropolitics and international relations. By situating the analysis within the context of persistent border disputes and asymmetric riparian positions, the paper highlights how water resources are being strategically mobilised to advance geopolitical objectives. The central research question posed is: Do China’s hydropower projects on the Brahmaputra River reflect a negative balancing strategy aimed at eroding India’s internal capabilities, and how does this affect prospects for green diplomacy and sustainable water security in the region? The study employs a qualitative analytical approach grounded in a case study research design, integrating documentary analysis of international reports, technical data, and peer-reviewed academic literature. China’s upstream initiatives – encompassing dam construction and hydrological data management – consolidate Beijing’s role as a hydro-hegemon, thereby exacerbating India’s vulnerability as a downstream riparian state. These vulnerabilities manifest through ecological risks, livelihood insecurity in Northeast India, and escalating geopolitical friction. Drawing on realism theory, and in particular the concept of negative balancing, the study demonstrates how China’s actions contribute to the erosion of India’s internal resource potential and the complication of bilateral trust. Simultaneously, the paper connects these challenges to the relevant United Nations Sustainable Development Goals, thereby proposing pathways toward substantive green diplomacy and sustainable water governance in the region. The findings underscore that hydropolitics is not merely an environmental concern but a multidimensional challenge encompassing sustainability, security, and diplomacy in an inextricably intertwined manner.